Effects of amlodipine on ischaemia/reperfusion injury in the rat testis. (10th August 2015) - Dogan, C.; Halici, Z.; Topcu, A.; Cadirci, E.; Karakus, E.; Bayir, Y.; Selli, J.
Summary: The aim of this study was to examine the effects of amlodipine (AML) in rat testicular torsion/detorsion damage. In this study, rats were divided into eight groups: (i) sham; (ii) testicular ischaemia, 2 h of ischaemia; (iii) testicular ischaemia/reperfusion (I/R), 2 h of ischaemia followed by 2 h of reperfusion; (iv) ischaemia + AML (5 mg kg −1 ) administered 30 min before ischaemia; (v) ischaemia + AML (10 mg kg −1 ) administered 30 min before ischaemia; (vi) and (vii) I/R + AML (5 mg kg −1 ) and I/R + AML (10 mg kg −1 ) administered 1.5 h after the induction of ischaemia, respectively, and at the end of a 2‐h ischaemia period and a 2‐h reperfusion period applied; and (viii) sham + AML (10 mg kg −1 ). Significant decreases in levels of superoxide dismutase and glutathione were observed in ischaemia and reperfusion groups when compared with healthy controls. These antioxidant levels increased in AML groups while malondialdehyde levels significantly decreased. While increases in tumour necrosis factor‐alpha and transforming growth factor‐beta levels were found in the torsion and detorsion groups, significant decreases in the levels of these inflammatory cytokines were observed in the treatment groups. These results demonstrate that AML significantly produced protective effects on testis tissue damage that occurs in the torsion/detorsion model via biochemical, histopathological and molecular pathways.